Moringa Leaf Extract (Moringa oleifera Lam.) as A Natural Preservative and Nutrient Source of Wet Noodles - Rachmawati, Sitti Rahayu; Suriawati, Junie (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2025)
Moringa leaves are high in nutritional value and contain antimicrobial phenolic chemicals, saponins, flavonoids, tannins, and steroids. Antimicrobials can be used as natural food preservatives. Wet noodles have a short shelf life at room temperature and low nutritional value. This study aims to determine the effect of the concentration of Moringa leaf extract on the durability and nutritional value of wet noodles. The research steps were carried out by making Moringa leaf extract is ussing the boiling method with water as a solvent. Moringa leaf extract concentrations of 0, 50, and 100% were substituted for making wet noodles and their preference level was observed through hedonic test. Furthermore, Moringa wet noodles were stored at room temperature 0, 1, 2, and 3 days and tested for microbial contamination, proximate nutritional value, and pH. The results showed that the best treatment was wet noodles substituted with 100% Moringa leaf extract can reduce the number of bacteria (9.60 x 105 cfu/g) according to SNI 7388-2009 (106 cfu/g) at room temperature storage for 1 (one) day, compared with wet noodles without Moringa leaf extract (4.05 x 106 cfu/g). Moringa leaf extract which is substituted can increase the nutritional value of wet noodles including ash content, fat, protein, and carbohydrates. The best treatment for hedonic test results is the 50% Moringa leaf extract substitution treatment because it is preferred by panelists in terms of aroma, color, texture, and taste.